Subject of Main Instruments (Violin) Madya Level Course In Music Study Program, Faculty of Languages and Arts, Universitas Negeri Surabaya - Moh Sarjoko (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Soprano violin is part of a stringed instrument. Today, the violin is one of the most popular musical instruments in the community. Many people learn this violin instrument in studios, music courses, schools and other educational institutions. Therefore, the need for the availability of this violin instrument is quite a lot. This also has an impact on the needs of teachers/tutors, the need for books/tools to support the ability to play the violin, and so on. Music Study Program, Faculty of Languages ​​and Arts, Universitas Negeri Surabaya is one of the educational institutions where many students choose the violin major specialization. This research is a class action research at the intermediate level elective principal instrument subject using the case study method through direct observation of the level of difficulty and suitability of the material, so that it can produce a book output. This book is a guide in learning the violin musical instrument which is equipped with techniques, scales, etudes, and repertoire for students of the Music Study Program, Faculty of Languages ​​and Arts, Universitas Negeri Surabaya who are taking the subject matter of violin at the intermediate level.